2011
DOI: 10.1007/s00246-011-9997-5
|View full text |Cite
|
Sign up to set email alerts
|

A Neonate with Left Congenital Diaphragmatic Hernia and Transient Retrograde Flow in the Aortic Arch

Abstract: Retrograde flow in the aortic arch identifies inadequate cardiac output in neonates with congenital heart disease. We present a left congenital diaphragmatic hernia (CDH) infant with retrograde flow in the arch that normalized after CDH repair. We hypothesize transient inadequacy of the left heart; prostaglandins might play a pivotal role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thankavel et al. reported a neonate with left CDH and a retrograde flow in the transverse arch 4 . The right‐to‐left shunt across the PDA directed the blood flow into the transverse arch in a retrograde fashion.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thankavel et al. reported a neonate with left CDH and a retrograde flow in the transverse arch 4 . The right‐to‐left shunt across the PDA directed the blood flow into the transverse arch in a retrograde fashion.…”
Section: Discussionmentioning
confidence: 98%
“…3 Thankavel et al reported a neonate with left CDH and a retrograde flow in the transverse arch. 4 The right-to-left shunt across the PDA directed the blood flow into the transverse arch in a retrograde fashion. In this case, there was a suspicion of coarctation of aorta with a z-score of aortic isthmus -2.64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation